2015
DOI: 10.1097/mph.0000000000000441
|View full text |Cite
|
Sign up to set email alerts
|

G6PC3 Deficiency

Abstract: Glucose-6-phosphatase catalytic subunit 3 (G6PC3) deficiency was recently defined as a new severe congenital neutropenia subgroup remarkable with congenital heart defects, urogenital malformations, endocrine abnormalities, and prominent superficial veins. Here, we report 3 patients with G6PC3 deficiency presenting with recurrent diarrhea, failure to thrive, and sinopulmonary infections leading to bronchiectasis. In patient I and II, a combined immune deficiency was suspected due to early-onset disease with lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…So far, there is no evidence that G6PC3 deficiency is a preleukaemic condition. In this review, we found only 1 case of leukaemia (P70) 8 ; no other reports of malignant transformation has been described in other SCN syndromes 5,9 …”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…So far, there is no evidence that G6PC3 deficiency is a preleukaemic condition. In this review, we found only 1 case of leukaemia (P70) 8 ; no other reports of malignant transformation has been described in other SCN syndromes 5,9 …”
Section: Discussionmentioning
confidence: 83%
“…Some G6PC3‐deficient patients may have a more profound immunological defect, and might require a deeper approach, including T cell flow cytometry and lymphoproliferation assays. When abnormalities in the function of T and B cells are demonstrated, it is mandatory to consider immunoglobulin replacement 9 . Progressive lymphopaenia has also been reported; therefore, immunological long‐term follow‐up is required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, there is no evidence that G6PC3 de ciency is a preleukemic condition. In this review, we found only one case of leukemia (P70) (8); no other reports of malignant transformation, as has been described in other SCN syndromes ( 5) (9). We have been able to include here most of the patients reported in the medical literature, expanding the phenotype, and describing the typical hematological and non-hematological features of G6PC3 de cient patients.…”
Section: Discussionmentioning
confidence: 92%